2011
DOI: 10.1007/s00595-011-4546-7
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase I expression in tumors as a biological marker for CPT-11 chemosensitivity in patients with colorectal cancer

Abstract: Irinotecan (CPT-11) is used as a first- and second-line chemotherapy for advanced or recurrent colorectal cancer (CRC). However, only 20%-30% of patients show an objective response to CPT-11 and the drug has severe toxicities, such as delayed-onset diarrhea, neutropenia, nausea, and vomiting. It is important to select patients who will demonstrate sensitivity to CPT-11 treatment to avoid unnecessary drug toxicities and to introduce anticancer treatment benefits to CRC patients. DNA topoisomerase I (Topo I) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 32 publications
0
24
1
Order By: Relevance
“…These results are not supported by the earlier hypothesis that lower expression of Topo-1 is correlated with a worse response to Topo-1 inhibitors. 36,37 However, results of other studies from Dutch colorectal cancer group failed to replicate the findings and concluded that although absolute Topo-1 expression may play a role, it is likely that additional pathways contribute to irinotecan sensitivity of Topo-1. 38,39 Therefore, these results indicate that clinical significance of Topo-1 is still unknown and remains controversial as prognostic marker.…”
Section: Numerous Preclinical and Clinical Studies Have Demonstrated contrasting
confidence: 47%
“…These results are not supported by the earlier hypothesis that lower expression of Topo-1 is correlated with a worse response to Topo-1 inhibitors. 36,37 However, results of other studies from Dutch colorectal cancer group failed to replicate the findings and concluded that although absolute Topo-1 expression may play a role, it is likely that additional pathways contribute to irinotecan sensitivity of Topo-1. 38,39 Therefore, these results indicate that clinical significance of Topo-1 is still unknown and remains controversial as prognostic marker.…”
Section: Numerous Preclinical and Clinical Studies Have Demonstrated contrasting
confidence: 47%
“…In current chemotherapeutic treatment for CRC, irinotecan (CPT-11), a semisynthetic derivative of camptothecin, is one of the key cytotoxic drugs with a 30% single agent response rate and 50% response rate when combined with other agents such as 5-Fu/leucovorin (LV) (2). However, more than 40% of patients treated with this drug have severe toxicities, such as diarrhea and neutropenia that limit its efficacy (3), and there remain many patients treated with CPT-11 who become resistant and exhibit further tumor progression despite their initial response (4). Thus, it remains important to search for novel agents for new combination treatments to enhance efficiency, reduce toxicities and avoid the progression of colorectal tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic regulation of topo-1 promoter is crucial for determining transcription factor binding (TFB), gene expression, and CPT-11 sensitivity in CRC cells [8]. However, most mCRC patients did not achieve an objective response [9]. Moreover, CPT-11 efficacy is burdened by a potentially severe toxicity.…”
Section: Introductionmentioning
confidence: 99%